Broadband reflection cholesteric liquid crystal film fabricated by near-infrared photothermal response technology. Issue 12 (26th September 2021) - Zhao, Limin; Shi, Weiting; Gan, Ping; Zhang, Xuetao; Cao, Hui; Wang, Huihui; Wang, Dong; Yang, Zhou; He, Wanli
ABSTRACT: A polyvinyl alcohol–modified copper sulphide (PVA-CuS) nanoparticlephotothermal film with modulated photothermal response properties is fabricated. Aliquid crystal cell with modulated photothermal conversion function is fabricated by using the glass substrate with this photothermal film as one side of this liquid crystal cell. In the formula of cholesteric liquid crystal (CLC), there is achiral compound with temperature-dependent helical twisting power and aultraviolet (UV)-polymerisable monomer. Therefore, under the irradiation of the near-infrared laser, the temperature of the sample gradually increases due to the photothermal conversion function of the liquid crystal cell, which causes the pitch of the CLC to gradually increase. Meanwhile, the liquid crystallinity polymerisable monomer polymerises under the irradiation of UV light to form apolymer network, and fix the pitch at each temperature section, then form anon-uniform distribution of the pitch to achieve broadband reflection. The influence of heating speed and UV light intensity is investigated under different modulation modes of near-infrared laser. GRAPHICAL ABSTRACT: uf0001